(untitled) (Bangladesh Journal of Nutrition, 2014)
A cross sectional study was conducted to observe the dietary pattern and nutritional status of a selected group of working children in Dhaka metropolitan city. The study was conducted on randomly selected 100 children from a school run by an NGO at Moghbazar in Dhaka engaged in child labor age ranging between 8 to 17 years. The socio-economic profile, anthropometric measurements and dietary pattern of children were assessed. Information on socio-economic conditions was collected by interviewing the respondents through questionnaire. Dietary intake of the respondents was collected by 24 hours recall method. While considering age, majority of the children (51%) belonged to the age group of <12 years. While considering Z-score, 17% respondents were stunted and 15% were underweight. According to gender distribution 30.0% of boys and 13.8% of girls were stunted, 30.0% of boys and 11.3% of girls were under weight. Girls were seen nutritionally well than the boys by HAZ and WAZ. According to the body mass index (BMI) 81% of the children were found to be thin, 18% were normal and only 1% was overweight. Average monthly income, family size, duration of occupation and household monthly income of the respondents were 430.73Tk, 3.68, 24.88, 8231.12Tk respectively. Energy intake of the children was 1120 ± 205 kcal which filled up only 60% of their RDA. Both groups of respondents (boys and girls) were consumed 85% of protein’s RDA. Fat and carbohydrate intake was 63% and 59% of RDA respectively. In both sex, calcium intake was inadequate (259± 184 mg) in terms of RDA. Boys fulfilled 46.3%i of vitamin A and girls fulfilled 32.1%> of RDA. Both groups fulfilled the RDA of Niacin, Zinc and Iron. Boys fulfilled 91.1% of vitamin C, 88.9% of thiamine and only 38.9% of Riboflavin whereas; girls fulfilled 77.8%, 92.2% and 42.2% only of RDA respectively. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 61-74